Banking system adjustment to shock: The Kenyan case of liquidity-profitability trade-offs - Jared Osoro; Kiplangat Josea (Kenya Bankers Association (KBA), 2022)
This paper has the dual objective of establishing whether episodes of market shocks necessarily trigger the choice between more liquidity and more profitability and ascertaining whether the post-shock recovery path is one of liquidity giving way to non-liquid assets growth and, therefore, more profitability that is accompanied by positive economic outcomes. Using annual bank-level data from 2002 to 2020 and a fixed-effects regression model within an unbalanced panel data framework, we establish that: (i) liquidityprofitability trade-offs exist and is amplified during period of shocks. The extent of those trade-offs is sensitive to bank-specific attributes, especially bank size. It is more pronounced among smaller banks than bigger ones (ii) The trade-offs ought to be seen beyond being self-preserving but as a necessary adjustment to assure general market stability and subsequent restoration of the positive finance-growth nexus in a calm environment. As a sufficient condition, the transition process requires a policy environment that is facilitative of real lending rates adjustments corresponding to the attendant risks as opposed to a sticky regime even on the back of expectations of a risk-based pricing mechanism being in place. Without policy disincentivizing the crowding-out, which is prevalent when asset quality is weakening, the transition after the shock to profitability aligned with the positive finance-growth nexus may be prolonged.
Keywords: 330